Molecular characterization of BjussuSP-I, a new thrombin-like enzyme with procoagulant and kallikrein-like activity isolated from Bothrops jararacussu snake venom - Sant'Ana, Carolina D.; Bernardes, Carolina P.; Izidoro, Luiz Fernando M.; Mazzi, Maurfcio V.; Soares, Sandro G.; Fuly, Andre L.; Zingali, Russolina B.; Magro, Angelo J. [UNESP]; Braz, Antonio S. K. [UNESP]; Fontes, Marcos R. M. [UNESP]; Stabeli, Rodrigo G.; Sampaio, Suely V.; et al. (Elsevier France-editions Scientifiques Medicales Elsevier, 2008)
A thrombin-like enzyme, named BjussuSP-I, isolated from Bothrops jararacussu snake venom, is an acidic single-chain glycoprotein with M-r = 61,000, pI similar to 3.8 and 6% sugar. BjussuSP-I shows high proteolytic activity upon synthetic substrates, such as S-2238 and S-2288. It also shows procoagulant and kallikrein-like activity, but is unable to act on platelets and plasmin. These activities are inhibited by specific inhibitors of this class of enzymes. The complete cDNA sequence of BjussuSP-I with 696 bp encodes open reading frames of 232 amino acid residues, which conserve the common domains of thrombin-like serine proteases. BjussuSP-I shows a high structural homology with other thrombin-like enzymes from snake venoms where common amino acid residues are identified as those corresponding to the catalytic site and subsites S1, S2 and S3 already reported. In this study, we also demonstrated the importance of N-linked glycans, to improve thrombin-like activity of BjussuSP-I toxin. (c) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: thrombin-like enzyme; Bothrops jararacussu; snake venom; proteolytic activity; cDNA; glycosylation; structural characterization